Variability and co-relationship of body traits in west African dwarf goats in a tropical humid enviroment - Jesuyon, Oluwatosin Mawunapon Adegoke (Array, 2019)
To understand variability and phenotypic association among body traits in West African Dwarf goats, morphological traits were examined based on location and sex. Two hundred and twenty-seven (227) goats in two Nigerian states were surveyed. Randomized complete block with Factorial treatment design, GLM, Pearson’s phenotypic correlation procedures of SAS® was employed. Morphological and index traits examined were body weight (BWT), hearth girth (HGH), diagonal trunk length (DTL), height at the withers (HWT), height at the rump (HRP); and Trunk length index (TLI), over-building index (OBI), body depth index (BDI), body breath index (BBI), withers-girth index (WGI), body-length index (BLI)and Weight-height index (WHI). BWT, DTL, TLI, OBI, BLI and WHI were influenced (P<0.05) by location, while DTL, TLI, OBI, BDI, BBI and BLI were influenced (P<0.05) by interaction of Location and Sex. Does recorded higher (P<0.05) BWT, TLI and BLI (27.75, 183.62 and 156.33), while Bucks had higher (P<0.05) DTL, HGH, HWT, HRP, OBI, BDI, BBI, WGI and WHI (80.57, 58.78, 46.89, 46.36, 99.29, 126.01, 127.01, -26.02 and 45.83). Ekiti goats recorded higher OBI, while Osun goats were higher on DTL, TLI, BLI and WHI (P<0.05). Highest correlation for females and males were between BWT/WHI (r =0.952/0.967, P<0.0001); for BWT/WHI were (r =0.969/0.972, 0.0001); and between HRP/HWT (r =0.953/0.929, P<0.0001) on Ekiti and Osun goats respectively. Between Ekiti and Osun goats BWT/WHI (r =0.969/0.972, P<0.0001) and HRP/HWT (r =0.953/0.929, P<0.0001) were obtained. CVs were highest on WGI (-69.65/-45.16); BWT (31.89/43.79), and WHI (29.25/35.54) for Does and Bucks; while WGI (-56.72/57.42), BWT (53.51/46.78) and WHI (42.09/36.76) were higher for Ekiti and Osun goats. Significant (P<0.0001) phenotypic correlation were obtained between BWT, DTL, HWT, HGH individually, and many other traits (r =0.336-0.957).